Against All Odds : Singapore's Successful Lobbying on the Cambodia Issue at the United Nations - Desker, Barry (ISEAS Publishing, 2016)
Vietnam's invasion and occupation of Cambodia on 25 December 1978 shattered the peace in Southeast Asia. The geo-political fabric of the region could have changed forever if nothing was done to oppose the invasion. Leading the charge was tiny Singapore, with her diplomats spearheading the thrust. Singapore could not do it alone, but had to have the support of like-minded nations from the region and beyond. Many sceptics, both within and outside Singapore, were convinced that Singapore's efforts would fail, as a tiny state could not possibly exert on the regional and global stage the kind of influence needed for the task. The Cambodia issue changed all that. Singapore and her diplomats, by their conviction and doggedness, took the lead in galvanizing international and regional support to thwart the occupation of Cambodia as a fait accompli by Vietnam. This paper tells the inside story of how Singapore's diplomats lobbied for ASEAN's interests in various international fora at a critical time in the region's history. The lessons learnt are still relevant today.